Corporate social responsibility in the work place: Experimental evidence on CSR from a gift-exchange game - Hannes Koppel; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We analyze the effect of investments in corporate social responsibility (CSR) on workers' motivation. In our experiment, a gift exchange game variant, CSR is captured by donating a certain share of profits to a charity. We are testing for CSR effects by varying the possible share of profits given away. Additionally, we investigate the effect of a mission match, i.e., a worker prefering the same charity the firm is actually donating to. Our results show that on average workers reciprocate investments into CSR with increased effort. A mission match does result in higher effort, but only when investment into CSR is high.
Keywords: C73; C91; D03; J01; M14; M52; 330; corporate social responsibility; gift-exchange game; experiment; labor market; incentives; Corporate Social Responsibility; Geschenk; Spieltheorie; Leistungsmotivation; Ökonomischer Anreiz; Test